2015
DOI: 10.1590/1982-43272560201511
|View full text |Cite
|
Sign up to set email alerts
|

CDRI as an Instrument to Evaluate Infants With Developmental Problems Associated With Autism

Abstract: This exploratory study investigates the contributions the Clinical Risk Indicators in Child Development (CDRI) may bring for the evaluation of infants who might be considered in autistic development. To do so, results of the evaluation -using CDRI and the Modified Checklist for Autism (M-CHAT) -of 43 babies who were 18 months old were compared. The present study showed that autism is amongst the risks the CDRI detects. The statistical analysis highlights that the axis Subject Assumption (SA) may not differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…When two or more items are absent, it may indicate the occurrence of psychic risk with a predictive value for mental problems or for child developmental problems at 3 years of age (Kupfer et al., ). Increased suffering results assessed with the IRDI were significantly associated with the presence of early signs of autism assessed with the Modified‐Checklist for Autism in Toddlers (Campana, Lerner, & David, ); the instrument has shown good sensitivity levels for autism in a study with children assessed by CARS (Machado, Lerner, Novaes, Palladino, & Cunha, ). Recent research has shown an association between children presenting early signs of psychological distress in the 0 to 18 months age range identified by the IRDI protocol and a lower quality of life from the psychosocial perspective at 6 years old (Paolo et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…When two or more items are absent, it may indicate the occurrence of psychic risk with a predictive value for mental problems or for child developmental problems at 3 years of age (Kupfer et al., ). Increased suffering results assessed with the IRDI were significantly associated with the presence of early signs of autism assessed with the Modified‐Checklist for Autism in Toddlers (Campana, Lerner, & David, ); the instrument has shown good sensitivity levels for autism in a study with children assessed by CARS (Machado, Lerner, Novaes, Palladino, & Cunha, ). Recent research has shown an association between children presenting early signs of psychological distress in the 0 to 18 months age range identified by the IRDI protocol and a lower quality of life from the psychosocial perspective at 6 years old (Paolo et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Seguindo uma proposta diferente dos outros protocolos, o Irdi identifica risco psíquico no desenvolvimento, dentre eles o autismo. Campana, Lerner & David (2015), após avaliarem 43 bebês de 18 meses, comparando M-CHAT e Irdi, identificaram que o protocolo Irdi também sinaliza risco para o autismo. O Irdi tem sido muito utilizado em pesquisas, tendo sido incluído na Caderneta de Saúde da Criança (Kupfer & Bernardino, 2018).…”
Section: Instrumentos Auxiliaresunclassified